2015
DOI: 10.1016/j.ijsu.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open approach in the management of appendicitis complicated exclusively with peritonitis: A single center experience

Abstract: Both approaches showed no differences in complications in the management of appendicitis complicated exclusively with peritonitis. In our experience, laparoscopic appendectomy is a safe approach in cases of appendicitis complicated exclusively with peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 19 publications
1
22
1
6
Order By: Relevance
“…In a randomized clinical study conducted by Taguchi et al 13 four cases of stump leakage were found in the closed appendiceal stump with the technique of bipolar endocoagulation in CA cases. The operative time in the studies by Taguchi et al 13 and Quezada et al 28 was longer than in our study. In our study, patients with an abscess had a longer operative time, which may explain the presence of appendiceal inflammatory processes, aspiration of abscess formation, irrigation, and a more difficult operation.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In a randomized clinical study conducted by Taguchi et al 13 four cases of stump leakage were found in the closed appendiceal stump with the technique of bipolar endocoagulation in CA cases. The operative time in the studies by Taguchi et al 13 and Quezada et al 28 was longer than in our study. In our study, patients with an abscess had a longer operative time, which may explain the presence of appendiceal inflammatory processes, aspiration of abscess formation, irrigation, and a more difficult operation.…”
Section: Discussioncontrasting
confidence: 65%
“…12,13,14,15,16,17 It may be reasonable to assume that the presence and proliferation of peritonitis may be a risk factor for POIAA, and therefore, necrotic perforated appendicitis in the intraabdominal space may have a lower risk of POIAA than cases complicated by peritonitis. 3,12,14,16,17,28 Another issue discussed is that abundant irrigation of the abdominal cavity with 0.9% saline solution is shown as one of the causes of abscess development. 3 In a clinical study performed by Katkhouda et al 17 the examination of the Douglas, irrigation, aspiration and the use of endobags removed abscesses and necrotic fragments from cavities and reduced the frequency of POIAA from 2.4% to 0.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,11] Moreover, LA has been shown to be safer in complicated AA than in open surgery; therefore, its use in the emergency setting is rising. [12][13][14][15][16] While challenging, discrimination between uncomplicated and complicated AA is clinically relevant as outcomes vary, with complicated cases faring worse. [17] Additionally, patients with uncomplicated AA may be successfully treated with antibiotics, in comparison to complicated cases, which practically always require an appendectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this method include decreased wound infections, a shorter postoperative recovery time, reduced time to return to normal activities, and a reduced need for postoperative analgesia (7)(8)(9). Open and laparoscopic appendicitis studies exist in the literature, but few have investigated the neuroendocrine response (10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%